2013
DOI: 10.1165/rcmb.2013-0069oc
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Signaling Modulates DNA Repair Response and Survival against Klebsiella pneumoniae Infection in Host Cells and in Mice

Abstract: Klebsiella pneumoniae causes serious infections in the urinary tract, respiratory tract, and blood. Lipid rafts, also known as membrane microdomains, have been linked to the pathogenesis of bacterial infection. However, whether lipid rafts affect K. pneumoniae internalization into host cells remains unknown. Here, we show for the first time that K. pneumoniae was internalized into lung cells by activating lipid rafts. Disrupting lipid rafts by methyl-b-cyclodextrin inhibited pathogen internalization, impairing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…We and others have also reported that hyperoxia induced DNA damage response (45) and other response mechanisms (46), which is tightly regulated by a variety of signaling system (4749). Additionally, the DNA repair response is also associated with oxidative cytotoxicity and tissue injury resulted from various triggering factors, including infection, chronic inflammation, trauma, and chemotherapeutic application (5056). Despite a variety of hyperoxic-mediated pathogenic factors contributing to tissue damage, we propose that increased generation and release of superoxide with hyperoxia contribute to the heightened pathophysiology in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have also reported that hyperoxia induced DNA damage response (45) and other response mechanisms (46), which is tightly regulated by a variety of signaling system (4749). Additionally, the DNA repair response is also associated with oxidative cytotoxicity and tissue injury resulted from various triggering factors, including infection, chronic inflammation, trauma, and chemotherapeutic application (5056). Despite a variety of hyperoxic-mediated pathogenic factors contributing to tissue damage, we propose that increased generation and release of superoxide with hyperoxia contribute to the heightened pathophysiology in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the involvement of flagellin in initiating inflammasome activation in Atg7 deficiency. However, we cannot exclude the possibility that other bacterial structural and virulence factors including type 3 secretion systems (T3SS), which may participate in the complex pathogenesis responsible for inflammation (4749). A recent report demonstrated that lipopolysaccharide (LPS) was delivered from gram-negative bacteria by outer membrane vesicles to the host cell cytosol and triggered caspase-11 activation (50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tuberculosis, dietary cholesterol appears to impact the pathogenesis of other types of pulmonary infections, including pneumonia. Klebsiella pneumoniae —a pneumonia-causing Gram-negative pathogen—additionally utilizes host lipid rafts for infection, whereas depletion of host cell cholesterol by MβCD and LXR activation impairs K. pneumonia internalization and subsequent host defenses [ 144 , 145 ]. These findings suggest that cholesterol enrichment may promote K. pneumonia clearance.…”
Section: Dietary Cholesterol Effects In Infectious Diseasementioning
confidence: 99%